Evaluación de las principales fincas productoras de queso fresco artesanal manaba sobre la preferencia sensorial, calidad fisicoquímica y microbiológica - Solórzano Zambrano, Virginia Guadalupe (2021)
The objective was to evaluate the fresh artisan manaba cheese and the main farms that produce it, on the variables of compliance with Good Milking Practices (BPO initials in Spanish), physicochemical, microbiological and sensory quality, an interview was applied as a tool to a sample of the sectors of higher cheese production and diagnoses of the observation files through which it was possible to know that all the farms presented non-compliance with the BPO and Good Manufacturing Practices (GMP), as established by the Ministry of Agriculture, Livestock and Fisheries (MAGAP initials in Spanish); then cheese samples were taken to evaluate sensory preference, determining the attributes: color (White), flavor (salty-medium), texture (soft) that was liked by potential consumers. Cheese samples were taken for the respective physicochemical analyzes (pH-acidity-humidity). These data were analyzed by analysis of variance which shows that for the variables, acidity there is no significant difference between the farms; and humidity indicates that there are significant differences, while for pH there are no significant differences (Sig <0.05); as far as farms 3 and 5 (pH 5.61- 5.48; acidity 0.15-0.16; humidity 66.06-65.61) presents a permissible range by the NSO-67.01.01.06 standard; the microbiological analyzes (Enterobacteria-E. coli-S. aureus) were evaluated using binary logistic regression that determined that there was no significant statistical difference between the cheese-producing farms, that is, any would have the same contamination in the cheese, showing that farms 3 and 5 comply with the INEN-1528 standard according to the maximum allowable index for E. coli, S. aureus and Enterobacteria respectively.